Interiors of the Mandapa (pillared hall) of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here are the interiors of the mandapa (pillared hall) of the Mahanaleshwar Temple. The centre of the mandapa has a slightly raised platform on which stand six pillars that eventually support the circular ceiling of the temple. The central pillars are of a fluted variety. The four corners of the mandapa that join the transepts to the antarala (vestibule or antechamber) and the mukhamandapa (front porch) to the transepts have ornamented jali (lattice) patterns.